An Extraordinary Case of Infective Endocarditis at its Extreme forms of Systemic Embolisation: A Rare Case Report - Adhikari, Suman; Gajurel, Ratna Mani; Paudel, Chandra Mani; Devkota, Surya; Shakya, Smriti; Koirala, Parash; Thapa, Shovit; Pathak, Surya Raj; Sharma, Manju; Yadav, Vijay (Nepalese Heart Journal, 2020)
The overall incidence of embolic complications in infective endocarditis (IE) ranges from 20 to 50%. It is very uncommon for a treating physician to encounter a patient having multiple manifestations of systemic embolisation.Acute coronary syndrome complicating infective endocarditis is an uncommon finding and the incidence has been found to be upto 10%.Cerebral embolism should be suspected in patients with infective endocarditis and neurological sign and symptoms. Neurologic manifestations can sometimes be the first presentation of infective endocarditis. We present the scenario of a 51-year-old diabetic male with chronic kidney disease, rheumatic heart disease with infective endocarditis leading to multiple embolic complications. Our case is notable because the patient had evidence of coronary, cerebral, splenic, hepatic and musculoskeletal manifestations due to embolic complications of IE within a duration of one year. Our case was primarily managed by multidiscipliniary approach. It is an impossible task for a cardiologist to treat such cases with showering complications where a multidisciplinary team approach is the only treatment option.